A Toddler With Uncontrollable Shaking After a Minor Fall. Issue 10 (October 2017) - Wu, Henry; Mody, Ameer P.
Abstract : Abstract: A toddler with a closed head injury six days prior to admission, recently diagnosed with post-concussive syndrome and acute otitis media presented to our emergency department with complaint of uncontrollable shaking of the head and extremities. Physical examination demonstrated dancing movements of the eyes and truncal ataxia, concerning for the diagnosis of opsoclonus-myoclonus syndrome. Magnetic resonance imaging study was consistent with a retroperitoneal mass that was confirmed as neuroblastoma by metaiodobenzylguanidine scan and later surgical resection. We present this case, accompanied by a video of the patient, to help the emergency physician recognize this rare and often misdiagnosed syndrome. Abstract : Supplemental digital content is available in the text.